Origin and geodynamic setting of Late Cenozoic granitoids in Sulawesi, Indonesia. (1st July 2016) - Maulana, Adi; Imai, Akira; Van Leeuwen, Theo; Watanabe, Koichiro; Yonezu, Kotaro; Nakano, Takanori; Boyce, Adrian; Page, Laurence; Schersten, Anders
Highlights: Three contrasting I-type granitoids series of Late Cenozoic age Sulawesi Island. Shoshonitic (HK), high-K calc-alkaline (CAK), calc-alkaline to tholeiitic (CA-TH) granitoids. Mod. mantle/crustal eq. (HK), continental fragment (CAK), lower crust (CA-TH). HK and most CAK granitoids are ilmenite-series. The northernmost CAK and CA-TH granitoids are magnetite-series. Abstract: Late Cenozoic granitoids are widespread in a 1600 km long belt forming the Western and Northern Sulawesi tectono-magmatic provinces. They can be divided into three rock series: shoshonitic (HK), high-K felsic calc-alkaline (CAK), and normal calc-alkaline to tholeiitic (CA-TH). Representative samples collected from eleven plutons, which were subjected to petrography, major element, trace element, Sr, Nd, Pb isotope and whole-rock δ 18 O analyses, are all I-type and metaluminous to weakly peraluminous. The occurrence of the two K-rich series is restricted to Western Sulawesi, where they formed in an extensional, post-subduction tectonic setting with astenospheric upwelling providing thermal perturbation and adiabatic decompression. Two parental magma sources are proposed: enriched mantle or lower crustal equivalent for HK magmas, and Triassic igneous rocks in a Gondwana-derived fragment thrust beneath the cental and northern parts of Western Sulawesi for CAK magmas. The latter interpretation is based on striking similarities in radiogenic isotope and trace element signatures. CA-TH granitoids are found mostly in Northern Sulawesi. Partial melting of lower-middle crust amphibolites in an active subduction environment is the proposed origin of these rocks. Fractional crystallization and crustal contamination have played a significant role in magma petrogenesis, particularly in the case of the HK and CAK series. Contamination by organic carbon-bearing sedimentary rocks of the HK and CAK granitoids in the central part of Western Sulawesi is suggested by their ilmenite-series (reduced) character. The CAK granitoids further to the north and CA-TH granitoids in Northern Sulawesi are typical magnetite-series (oxidized). This may explain differences in mineralization styles in the two regions.